Investigating Factors Affecting of the Occurrence of Suicides Leading to Death in Bodies Referred to the Forensic Medicine Organization of Tehran Province from 2010 to 2019 - Mohammad Hossein Sadeghian; Seyed Amirhossein Mahdavi; Farhad Habibi; Masoud Shafiei (Tehran University of Medical Sciences, 2022)
Background and Aim: The American Psychiatric Association identifies suicide as the third leading cause of death among people aged 15 to 24. This study was conducted with the aim of investigating factors affecting of the occurrence of suicides leading to death in corpses referred to the Forensic Medicine Organization of Tehran Province from 2010 to 2019. Materials and Methods: This research was a descriptive and analytical cross-sectional study in 2019 year. The statistical population includes all bodies referred to forensic medicine. The information related to all corpses referred to forensic medicine which was analyzed between 2010 and 2019 were 5471 cases. Descriptive and analytical statistical methods were used to analyze the data. P-value less than 0.05% was considered valid. Results: The results showed that 50% of suicide deaths were under 32 years old. Sixty-nine point two percent of suicides leading to death are male and the rest are female. The highest frequency in terms of method was related to the hanging method, 39.3%, and in the youth age group, in terms of the level of education in men, high school diploma and diploma in women. The highest frequency of suicide related to singles was 47.1% and 27.4% in the summer season. The most common method of suicide was hanging, with more than 39%, followed by poisoning with poison, with more than 25% of cases. The least used method was drowning. Conclusion: Based on the results of this study, it seems that factors such as age, sex, level of education, and even geographic and social factors are among the factors that affect suicide, which can help policymakers, managers, psychologists, psychiatrists, and related organizations. Paying attention to educational literacy, employment status and income level of people, special attention of families to adolescent and young boys and girls and especially their marital status can be effective measures to prevent suicide.